2017
DOI: 10.1007/s11684-017-0547-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Ginkgo biloba extract and Ginkgolide B against oxygen–glucose deprivation/reoxygenation and glucose injury in a new in vitro multicellular network model

Abstract: Acute ischemic stroke (AIS), as the third leading cause of death worldwide, is characterized by its high incidence, mortality rate, high incurred disability rate, and frequent reoccurrence. The neuroprotective effects of Ginkgo biloba extract (GBE) against several cerebral diseases have been reported in previous studies, but the underlying mechanisms of action are still unclear. Using a novel in vitro rat cortical capillary endothelial cell-astrocyte-neuron network model, we investigated the neuroprotective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 41 publications
1
58
1
Order By: Relevance
“…EGb761 is widely used in treating cardiovascular, neurological, endocrinological and immunological disorders . Furthermore, its safety and effectiveness in clinical use have been well recognized and its adverse effects are rare .…”
Section: Discussionmentioning
confidence: 99%
“…EGb761 is widely used in treating cardiovascular, neurological, endocrinological and immunological disorders . Furthermore, its safety and effectiveness in clinical use have been well recognized and its adverse effects are rare .…”
Section: Discussionmentioning
confidence: 99%
“…Ginkgo biloba (Ginkgoaceae) is an ancient Chinese tree, extensively cultivated for traditional and medical purposes. G. biloba extract contains flavonol glycosides, bilobalide, terpene trilactones, and varied forms of ginkgolides, and ginkgolic acid (Müller et al, 2012;Yang et al, 2018). In Europe, the standardized form of G. biloba extract is broadly used to improve the therapeutic condition of patients with various forms of dementia (Maurer et al, 1997;Luo, 2001).…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…43 It has also been shown that Ginkgo bioactive agents as ginkgolides and bilobalide exert beneficial effects in animal models of acute neurodegeneration induced mainly by hypoxia and ischemia. [44][45][46] Mdzinarishvili et al, 47 showed that pre-treatment with EGb761 extracts strongly reduce cellular oedema formation and neurodegeneration under ischemia conditions and that the mechanism could be related to a reduction of excitotoxicity due to high glutamate release during ischemia.…”
Section: Ginkgo Bilobamentioning
confidence: 99%